Cathode active material for lithium secondary battery, cathode for lithium secondary battery, lithium secondary battery, and method for producing cathode active material for lithium secondary battery
By using Li, Ni and Element X in a specific composition proportion in the positive electrode active material of lithium-ion batteries and using specific process processing, the problem of poor cycle performance of lithium-ion batteries under high temperature conditions is solved, and excellent high-temperature cycle characteristics are achieved.
Patent Information
- Application Number
- JP2023154116
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-02
AI Technical Summary
Existing lithium-ion batteries have poor cycle performance under high temperature conditions, making it difficult to meet the needs of improving high-temperature cycle characteristics.
A positive electrode active material composed of Li, Ni and element X (where X is a elements such as Co, Al, Mg, Ca, Si, Fe, Cr, V, Mo, W, Nb, Ti, Zr, Ta, Mn, B, etc.) is prepared by specific compositional proportions and process processing.
It realizes excellent cycle performance of lithium-ion batteries under high temperature conditions and improves the battery's high temperature cycle stability.
Smart Images

Figure 2025045996000002 
Figure 2025045996000003 
Figure 2025045996000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a positive electrode for a lithium secondary battery, a lithium secondary battery, and a method for producing a positive electrode active material for a lithium secondary battery. [Background technology]
[0002] In a lithium secondary battery, an electrolyte (such as a non-aqueous electrolyte or a solid electrolyte) is disposed between a positive electrode and a negative electrode. In a lithium secondary battery, charging and discharging are performed by lithium ions moving between the positive electrode and the negative electrode via the electrolyte.
[0003] In the lithium secondary battery, the positive electrode is produced by using a positive electrode active material including, for example, a lithium metal composite oxide. The positive electrode active material for lithium secondary batteries is produced by, for example, firing a mixture of a metal composite compound, which is a precursor of the lithium metal composite oxide, and a lithium compound.
[0004] Conventionally, various positive electrode active materials have been proposed to improve the performance of lithium secondary batteries (see, for example, Patent Document 1 and Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2018-49685 A [Patent Document 2] WO2020-175552 Summary of the Invention [Problem to be solved by the invention]
[0006] There is a demand for improved cycle characteristics at high temperatures in lithium secondary batteries.
[0007] Accordingly, an object of the present invention is to provide a positive electrode active material for a lithium secondary battery, a positive electrode for a lithium secondary battery, a lithium secondary battery, and a method for manufacturing a positive electrode active material for a lithium secondary battery, which can easily realize a lithium secondary battery having excellent cycle characteristics at high temperatures. **Means for Solving the Problems**
[0008] The present invention has the following aspects. [1] A positive electrode active material for a lithium secondary battery, comprising Li, Ni, and element X in its composition, wherein the element X is at least one element selected from the group consisting of Co, Al, Mg, Ca, Si, Fe, Cr, V, Mo, W, Nb, Ti, Zr, Ta, Mn, and B, and the molar amounts [Li], [Ni], and [X] of Li, Ni, and the element X satisfy the relationships shown in the following (Equation A1) to (Equation A3), and in a differential thermal analysis curve obtained by performing differential thermal analysis on a positive electrode mixture contained in the lithium secondary battery after charging the lithium secondary battery fabricated using the positive electrode active material for a lithium secondary battery at 4.3 V (vs. Li / Li) and then in an inert gas atmosphere, there are a first peak top located at a first temperature and a second peak top located at a second temperature higher than the first temperature in a temperature range of 150°C or higher and 300°C or lower. A positive electrode active material for a lithium secondary battery. [Li]:[Ni]:[X]=a:(1 - b):b …(Equation A1) 0.95 ≦ a ≦ 1.2 …(Equation A2) 0 < b ≦ 0.3 …(Equation A3) [2] The positive electrode active material for a lithium secondary battery according to [1], wherein the second temperature T2 satisfies the relationship shown in the following (Equation B). 235°C ≦ T2 ≦ 285°C …(Equation B) [3] The first temperature T1 and the second temperature T2 satisfy the relationship shown in the following (Formula C). The positive electrode active material for a lithium secondary battery according to [1] or [2]. 1.06 ≦ T2 / T1 ≦ 1.40 … (Formula C) [4] The peak intensity P1 of the first peak top and the peak intensity P2 of the second peak top satisfy the relationship shown in the following (Formula D). The positive electrode active material for a lithium secondary battery according to any one of [1] to [3]. 0 < P2 / P1 ≦ 1.0 … (Formula D) [5] The c-axis length L of the positive electrode active material for a lithium secondary battery satisfies the relationship shown in the following (Formula E). The positive electrode active material for a lithium secondary battery according to any one of [1] to [4]. 14.160 Å ≦ L ≦ 14.210 Å … (Formula E) [6] 50% cumulative volume particle size D 50 satisfies the relationship shown in the following (Formula F). The positive electrode active material for a lithium secondary battery according to any one of [1] to [5]. 5 μm ≦ D 50 ≦ 25 μm … (Formula F) [7] Having the positive electrode active material for a lithium secondary battery according to any one of [1] to [6]. A positive electrode for a lithium secondary battery. [8] Having the positive electrode for a lithium secondary battery according to [7]. A lithium secondary battery.
Advantages of the Invention
[0009] According to the present invention, it is possible to provide a positive electrode active material for a lithium secondary battery, a positive electrode for a lithium secondary battery, a lithium secondary battery, and a method for manufacturing a positive electrode active material for a lithium secondary battery, which can easily realize a lithium secondary battery having excellent cycle characteristics at high temperatures.
Brief Description of the Drawings
[0010] [Figure 1] FIG. 1 is a diagram showing an example of a differential thermal analysis curve (DTA curve) of the CAM in the embodiment. [Diagram 2] FIG. 2 is a flow diagram showing an overview of a manufacturing method for producing a CAM according to an embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing an example of a lithium secondary battery. [Figure 4] FIG. 4 is a schematic diagram showing an example of an all-solid-state lithium secondary battery. [Diagram 5] FIG. 5 is a diagram showing differential thermal analysis curves (DTA curves) obtained for (Example 1) and (Example C1). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] An example of an embodiment of the present invention will now be described.
[0012] In this specification, abbreviations are used for terms as appropriate. Specifically, metal composite compounds are abbreviated as "MCC" (Metal Composite Compound). Positive electrode active materials for lithium secondary batteries are abbreviated as "CAM" (Cathode Active Material for lithium secondary batteries). In addition, "Ni" and "Li" do not refer to nickel metal or lithium metal alone, but to Ni element or Li element. The same applies to other elements such as Co and Mn.
[0013] [A]CAM In this embodiment, the CAM contains a lithium metal composite oxide (abbreviated as LiMO). The CAM may contain a residue (e.g., LiOH, Li2CO3) remaining in LiMO during the preparation of LiMO, or a coating layer containing Li and at least one element selected from the group consisting of Nb, Ge, Si, P, Al, W, Ta, Ti, S, Zr, Zn, V, and B.
[0014] [A-1] Crystal structure In this embodiment, the CAM is a layered structure.
[0015] The crystal structure of CAM is a layered rock salt type structure, and is preferably a hexagonal type or a monoclinic type. The hexagonal type crystal structure is P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P62, P64, P6 The monoclinic crystal structure is assigned to one space group selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c, and C2 / c. Among the above, the crystal structure of CAM is particularly preferably a hexagonal type belonging to the space group R-3m or a monoclinic type belonging to the space group C2 / m in order to obtain a lithium secondary battery having a high discharge capacity.
[0016] [A-2] Composition In this embodiment, the CAM contains at least Li, Ni, and an element X in its composition.
[0017] Here, element X is at least one element selected from the group consisting of Co, Al, Mg, Ca, Si, Fe, Cr, V, Mo, W, Nb, Ti, Zr, Ta, Mn, and B. Element X is preferably at least one element selected from the group consisting of Co, Al, Mg, Ca, W, Nb, Ti, Zr, Mn, and B. Further, element X preferably consists of at least one element selected from the group consisting of Co, Al, and Mn and at least one element selected from the group consisting of Mg, Ca, Si, Fe, Cr, V, Mo, W, Nb, Ti, Zr, Ta, and B.
[0018] The amount of substance of Li [Li], the amount of substance of Ni [Ni], and the amount of substance of element X [X] contained in CAM satisfy the relationships shown in the following (Formula A1) to (Formula A3) (a = [Li] / ([Ni]+[X])).
[0019] [Li]:[Ni]:[X]=a:(1-b):b …(Formula A1) 0.95≦a≦1.2 …(Formula A2) 0<b≦0.3 …(Formula A3)
[0020] By satisfying the relationships shown in (Formula A1) to (Formula A3), the cycle characteristics of the lithium secondary battery at high temperature can be improved. It is more preferable that CAM satisfies the relationship shown in the following (Formula A2a), still more preferable that it satisfies the relationship shown in the following (Formula A2b), and particularly preferable that it satisfies the relationship shown in the following (Formula A2c).
[0021] 1.00≦a≦1.15 …(Formula A2a) 1.03≦a≦1.12 …(Formula A2b) 1.05≦a≦1.11 …(Formula A2c)
[0022] Incidentally, the composition of the substance is measured using, for example, an ICP emission spectroscopic analyzer (such as Optima7300 manufactured by PerkinElmer, Inc.). The measurement of the composition is carried out by performing a process of dissolving the sample in an acid or an alkali according to the element to be measured.
[0023] [A-3] Peak top in differential thermal analysis curve In this embodiment, the CAM is used to manufacture a lithium secondary battery at 4.3 V (vs. Li + In a differential thermal analysis curve (DTA curve) obtained by charging the positive electrode mixture contained in the lithium secondary battery with a lithium secondary battery containing 0.1% by weight of 100% by weight of 100% by weight of Li and then subjecting the positive electrode mixture contained in the charged lithium secondary battery to differential thermal analysis (DTA) in an inert gas (e.g., nitrogen gas) atmosphere, the positive electrode mixture has two peak tops in a temperature range of 150°C or more and 300°C or less.
[0024] Figure 1 shows an example of a DTA curve for CAM. In Figure 1, the horizontal axis shows temperature (°C), and the vertical axis shows the value (differential heat) (μV / mg) measured based on the temperature difference between a measurement sample and a reference substance. The DTA curve is an observation method for capturing changes in the thermal properties of a sample from the calorific value difference between the sample and the reference substance.
[0025] As shown in FIG. 1, the CAM of this embodiment has two peak tops in a temperature range of 150° C. or more and 300° C. or less. The two peak tops are a first peak top PT1 located at a first temperature T1 and a second peak top PT2 located at a second temperature T2 higher than the first temperature T1. As shown in FIG. 1, the first peak top PT1 has a peak intensity P1, and the second peak top PT2 has a peak intensity P2. For the peak intensities P1 and P2, values obtained by subtracting the baseline Tf and analyzing the first peak top PT1 and the second peak top PT2 from the baseline Tf by Gaussian fitting are used.
[0026] In the DTA curve, T1 and T2 are in the temperature range of 150°C to 300°C. This indicates that Li exists at two different sites, and the temperature at which it decomposes is different for each site. The existence of a structural region in which Li is introduced at different sites increases the structural stability of the CAM during lithium ion insertion and removal, improving the cycle characteristics of lithium secondary batteries at high temperatures.
[0027] The charging is performed on a lithium secondary battery having a positive electrode prepared using the above-mentioned CAM. The lithium secondary battery is then disassembled to recover a positive electrode mixture containing CAM. A differential thermal analysis is then performed on the recovered positive electrode mixture using, for example, a simultaneous differential thermal and thermogravimetric analyzer. The differential thermal analysis is performed under conditions that allow evaluation of the thermal decomposition of CAM. That is, the differential thermal analysis is performed under conditions that do not cause thermal decomposition of the conductive material (e.g., acetylene black) and binder (e.g., polyvinylidene fluoride (PVdF)) that constitute the positive electrode of the lithium secondary battery.
[0028] In addition, in this specification, "having a peak top" means that, in a differential curve created by differentiating a DTA curve, among points at which the differential value is zero, there are points before and after the point at which the differential value inverts from positive to negative.
[0029] [A-3-1] Regarding the second temperature T2 In the DTA curve of the CAM of this embodiment, it is preferable that T2 satisfies the relationship shown in the following (Formula B).
[0030] 235℃≦T2≦285℃…(Formula B)
[0031] It is more preferable that the relationship shown in the following formula Ba is satisfied.
[0032] 240℃≦T2≦280℃ …(Formula Ba)
[0033] [A-3-2] Relationship between the first temperature T1 and the second temperature T2 In the DTA curve of the CAM of this embodiment, it is preferable that T1 and T2 satisfy the relationship shown in the following (Formula C).
[0034] 1.06≦T2 / T1≦1.40…(Formula C)
[0035] The CAM more preferably satisfies the relationship shown in the following (Formula Ca), and still more preferably satisfies the relationship shown in the following (Formula Cb).
[0036] 1.08 ≦ T2 / T1 ≦ 1.38 …(Formula Ca) 1.10 ≦ T2 / T1 ≦ 1.35 …(Formula Cb)
[0037] [A-3-3] Regarding the relationship between peak intensity P1 and peak intensity P2 In the DTA curve of the CAM of the present embodiment, P1 and P2 preferably satisfy the relationship shown in the following (Formula D).
[0038] 0 < P2 / P1 ≦ 1.0 …(Formula D)
[0039] When the CAM satisfies the relationship shown in the above formula (C), since the layer in which Li exists at the site and the layer in which Li exists at a site different from R-3m are present in an appropriate (preferred) ratio, the cycle characteristics of the lithium secondary battery at high temperature can be further improved. The CAM more preferably satisfies the relationship shown in the following (Formula Da), and still more preferably satisfies the relationship shown in the following (Formula Db).
[0040] 0 < P2 / P1 ≦ 0.9 …(Formula Da) 0 < P2 / P1 ≦ 0.8 …(Formula Db)
[0041] [A-4] c-axis length L In the present embodiment, the c-axis length L of the CAM preferably satisfies the relationship shown in the following (Formula E).
[0042] 14.160 Å ≦ L ≦ 14.210 Å …(Formula E)
[0043] When the CAM satisfies the relationship shown in (Formula E), the stability of the crystal structure of the CAM increases, and the cycle characteristics at high temperature can be further improved. The CAM more preferably satisfies the following (Formula Ea).
[0044] 14.160Å≦L≦14.190Å…(Formula Ea)
[0045] The c-axis length L of CAM can be calculated by the following method. First, an X-ray diffractometer is used to perform powder X-ray diffraction measurement on CAM to obtain a powder X-ray diffraction pattern. Then, the above powder X-ray diffraction pattern is analyzed using integrated powder X-ray analysis software, and the crystal structure is refined in a layered rock salt structure belonging to the space group R-3m, whereby the c-axis length L is obtained.
[0046] [A-5] 50% cumulative volumetric particle size D 50 In this embodiment, the CAM is a powder in which a plurality of particles are aggregated. The CAM powder is a fired product, which will be described in detail later.
[0047] The CAM powder may be composed only of secondary particles formed by agglomeration of primary particles, or may be a mixture of primary particles and secondary particles. For example, the CAM powder may contain CAM primary particles and secondary particles formed by agglomeration of multiple primary particles.
[0048] The above-mentioned "primary particles" are particles that have no grain boundaries when the CAM is observed with a microscope (such as a scanning electron microscope) at a magnification of 1000 to 30000. The above-mentioned "secondary particles" are aggregates of the primary particles.
[0049] CAM is the 50% cumulative volumetric grain size D 50 It is preferable that the relationship shown in the following (Formula F) is satisfied.
[0050] 5μm≦D 50 ≦25μm…(Formula F)
[0051] When CAM satisfies the relationship shown in the above formula (F), the bulk density of CAM can be increased, and thus the packing density can be increased. As a result, in the positive electrode for lithium secondary batteries, the contact area between the CAM particles and the conductive material particles is increased, and the direct current resistance can be reduced, so that the cycle characteristics of the lithium secondary battery at high temperatures can be further improved. It is more preferable that CAM satisfies the following formula (Fa), and even more preferable that CAM satisfies the following formula (Fb).
[0052] 5μm≦D 50 ≦20μm …(Formula Fa) 5μm≦D 50 ≦19μm…(Formula Fb)
[0053] In addition, D 50 (μm) corresponds to the particle diameter value at 50% accumulation from the fine particle side in the cumulative particle size distribution curve. 50 is measured by a laser diffraction scattering method.
[0054] [B]CAM manufacturing method A manufacturing method for producing the CAM of this embodiment will be described.
[0055] FIG. 2 is a flow diagram showing an overview of a manufacturing method for producing a CAM according to an embodiment.
[0056] When producing the CAM of the embodiment, as shown in FIG. 2, a mixing step (ST10), a firing step (ST20), a post-treatment step (ST40), and a drying step (ST50) are carried out in this order.
[0057] [B-1] Mixing process (ST10) In the mixing step (ST10), a mixture containing MCC, which is a precursor of CAM, and a lithium compound is prepared. The mixture may contain a compound other than MCC and a lithium compound, for example, a zirconium compound such as zirconium oxide.
[0058] The mixture contains MCC and a lithium compound such that the amount of substance of Li ([Li]), the amount of substance of Ni ([Ni]), and the amount of substance of element X ([X]) satisfy the relationships shown in the following (Formula G1) to Formula (G3) (a0 = [Li] / ([Ni] + [X])). That is, when producing CAM having a desired amount of substance of Li (a in the above Formula (A1)), MCC and a lithium compound are mixed so as to satisfy the above Formula (G1) to Formula (G3) to obtain a mixture.
[0059] [Li]:[Ni]:[X]=a0:(1 - b):b …(Formula G1) 0 < a0 - a ≤ 0.10 …(Formula G2) 1.05 ≤ a0…(Formula G3)
[0060] By using a mixture that satisfies the relationships shown in (Formula G1) to (Formula G3), CAM having two peak tops in the temperature range of 150°C or higher and 300°C or lower in the aforementioned DTA curve can be easily produced. As a result, the cycle characteristics of the lithium secondary battery at high temperatures can be improved.
[0061] [B - 1 - 1]MCC MCC is a substance containing Ni and element X that constitute CAM, and is, for example, a metal composite hydroxide, a metal composite oxide, or a mixture thereof.
[0062] The metal composite hydroxide used as MCC is produced, for example, by a known batch coprecipitation method or a continuous coprecipitation method.
[0063] Hereinafter, a method for producing a metal composite hydroxide containing Ni, Co, and Mn as metal elements will be described in detail as an example.
[0064] Specifically, a nickel salt solution, a cobalt salt solution, a manganese salt solution, and a complexing agent are reacted by the continuous coprecipitation method described in JP - A - 2002 - 201028. Thereby, a metal composite hydroxide containing Ni, Co, and Mn (Ni (1-x-y) Co x Mn y(OH)2) is produced.
[0065] The nickel salt that is the solute of the nickel salt solution is, for example, at least one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate.
[0066] The cobalt salt that is a solute of the cobalt salt solution is, for example, at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate.
[0067] As the manganese salt which is the solute of the manganese salt solution, for example, at least one of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate can be used.
[0068] When producing a metal composite hydroxide containing Al, the aluminum salt that is the solute of the aluminum salt solution used is, for example, at least one of aluminum sulfate, aluminum nitrate, aluminum chloride, and aluminum acetate.
[0069] The above metal salts are the (Ni (1-x-y) Co x Mn y (OH)2). That is, in the mixed solution containing the above metal salts, the molar ratio of each element corresponds to (1-xy):x:y. Here, water is used as the solvent.
[0070] In the process for producing the metal composite hydroxide, a complexing agent may be used. In this case, the amount of the complexing agent is, for example, a molar ratio of the complexing agent to the total number of moles of the metal salts (nickel salt, cobalt salt, and manganese salt) that is greater than 0 and less than or equal to 2.0.
[0071] The complexing agent is a material capable of forming a complex with nickel ions, cobalt ions, and manganese ions in an aqueous solution, and is, for example, at least one of an ammonium ion donor (ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium fluoride, etc.), hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracil diacetic acid, and glycine.
[0072] In the co-precipitation method, the pH value of a mixture containing a nickel salt solution, a cobalt salt solution, a manganese salt solution, and a complexing agent is adjusted by adding an alkali metal hydroxide to the mixture before the pH of the mixture becomes neutral from alkaline. The alkali metal hydroxide is, for example, sodium hydroxide or potassium hydroxide.
[0073] In this case, the pH value is measured when the temperature of the mixed liquid is 40°C. The pH of the mixed liquid is measured when the temperature of the mixed liquid sampled from the reaction tank reaches 40°C. If the sampled mixed liquid is below 40°C, the mixed liquid is heated to 40°C and then the pH is measured. If the temperature of the sampled mixed liquid exceeds 40°C, the mixed liquid is cooled to 40°C and then the pH is measured.
[0074] In addition to the nickel, cobalt and manganese salt solutions, a complexing agent is continuously fed to the reaction vessel, whereby the reaction takes place and (Ni (1-x-y) Co x Mn y (OH)2) is produced.
[0075] Here, the temperature of the reaction vessel is controlled, for example, within a range of 20°C or higher and 80°C or lower, preferably within a range of 30°C or higher and 70°C or lower.
[0076] During the reaction, the pH value in the reaction tank is controlled within the range of, for example, pH 9 or more and pH 13 or less.
[0077] The reaction precipitate formed in the reaction tank is neutralized while being stirred. The time for neutralizing the reaction precipitate is, for example, in the range of 1 hour to 20 hours.
[0078] As a reaction vessel used in the continuous coprecipitation method, a reaction vessel having an overflow can be used in order to separate the formed reaction precipitate.
[0079] When producing a metal composite hydroxide by a batch coprecipitation method, an apparatus is used that includes a reaction tank without an overflow pipe and a concentration tank connected to the overflow pipe, and has a mechanism for concentrating the overflowed reaction precipitate in the concentration tank and circulating it back to the reaction tank.
[0080] Here, various gases (for example, inert gases such as nitrogen, argon, or carbon dioxide, oxidizing gases such as air or oxygen, or a mixture thereof) may be supplied into the reaction vessel.
[0081] After the reaction is completed, the neutralized reaction precipitate is isolated. The isolation is carried out, for example, by dehydrating the slurry containing the reaction precipitate (i.e., the coprecipitate slurry) by centrifugation, suction filtration, or the like.
[0082] The isolated reaction precipitate is then washed, dehydrated, dried and sieved in that order to obtain a metal composite hydroxide.
[0083] The reaction precipitate is preferably washed using water or an alkaline washing solution. In washing the reaction precipitate, an alkaline washing solution is preferably used, and in particular, an aqueous sodium hydroxide solution is preferably used as the alkaline washing solution. Washing may also be performed using a washing solution containing elemental sulfur. The washing solution containing elemental sulfur is, for example, an aqueous solution of potassium or sodium sulfate.
[0084] In the above example, a metal composite hydroxide is produced as MCC, but a metal composite oxide may also be prepared.
[0085] The metal composite oxide is produced, for example, by subjecting a metal composite hydroxide to a heat treatment. The heating step may be carried out multiple times as necessary. In the heating step, the heating temperature means the set temperature of the heating device, and when multiple heating steps are carried out, the heating temperature means the temperature at which heating is carried out at the highest holding temperature among the multiple heating steps.
[0086] The heating temperature is preferably in the range of 400°C or more and 700°C or less, and more preferably in the range of 450°C or more and 680°C or less.
[0087] The time for which the heating temperature is maintained in the heating step is in the range of 0.1 to 20 hours, and preferably in the range of 0.5 to 10 hours. The heating rate for increasing the temperature to the above-mentioned heating temperature is, for example, in the range of 50° C. / hour to 400° C. / hour. The heat treatment is carried out in a heating atmosphere containing air, oxygen, nitrogen, argon, or a mixed gas thereof.
[0088] The inside of the heating device may be an oxygen-containing atmosphere containing a moderate amount of oxygen. The oxygen-containing atmosphere may be a mixed gas atmosphere of an inert gas and an oxidizing gas, or may be an inert gas atmosphere in the presence of an oxidizing agent.
[0089] The oxygen-containing atmosphere need only have a sufficient amount of oxygen atoms present to oxidize the transition metal.
[0090] When the oxygen-containing atmosphere is a mixed gas atmosphere containing an inert gas and an oxidizing gas, the atmosphere in the heating device is controlled by a method of passing an oxidizing gas through the heating device or a method of bubbling an oxidizing gas through the mixed liquid.
[0091] The oxidizing agent present in the oxygen-containing atmosphere may be a peroxide such as hydrogen peroxide, a peroxide salt such as permanganate, a perchlorate, a hypochlorite, nitric acid, a halogen, or ozone.
[0092] [B-1-2] Lithium compounds The lithium compound used in the production of CAM is, for example, at least one powder of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium oxide, lithium chloride, and lithium fluoride. Of these, it is preferable to use either lithium hydroxide or lithium carbonate, or a mixture of both, as the lithium compound.
[0093] [B-2] Firing process (ST20) In the firing step (ST20), the mixture prepared in the mixing step (ST10) is fired to produce a fired product.
[0094] The firing temperature is not particularly limited, but is preferably in the range of 650° C. to 900° C., more preferably in the range of 680° C. to 850° C., and particularly preferably in the range of 700° C. to 820° C. If the firing temperature is 650° C. or higher, a CAM having a strong crystal structure can be obtained. Also, if the firing temperature is 900° C. or lower, the volatilization of lithium ions on the particle surface of the CAM can be reduced.
[0095] The retention time during firing is preferably 3 hours or more and 50 hours or less, more preferably 4 hours or more and 20 hours or less. When the retention time during firing is 50 hours or less, it is possible to prevent the deterioration of battery performance due to the volatilization of lithium ions. When the retention time during firing is 3 hours or more, the crystals are sufficiently developed, and the battery performance is excellent. The retention time during firing is appropriately adjusted depending on the type of transition metal element used and the type and amount of the precipitating agent.
[0096] In this embodiment, the rate of temperature rise to reach the maximum firing temperature is preferably 80° C. / hour or more, more preferably 100° C. / hour or more, and particularly preferably 150° C. / hour or more. The rate of temperature rise to reach the maximum firing temperature is calculated from the time from the start of temperature rise to the time when the holding temperature is reached in the firing device.
[0097] The firing step preferably has a plurality of firing stages with different firing temperatures. For example, the firing step preferably has a first firing stage and a second firing stage in which firing is performed at a higher temperature than the first firing stage. Furthermore, the firing step may have firing stages with different firing temperatures and firing times.
[0098] The firing step is carried out in a firing atmosphere that may include air, oxygen, nitrogen, argon, or a mixture thereof, depending on the desired composition.
[0099] The mixture of MCC and the lithium compound may be sintered in the presence of an inactive flux. The inactive flux may be added to such an extent that the initial capacity of the battery using CAM is not impaired, and may remain in the sintered product. As the inactive flux, for example, those described in WO2019 / 177032A1 can be used.
[0100] The mixture may be subjected to a pre-baking step before the above-mentioned baking step. In the pre-baking step, the mixture is pre-baked at a temperature lower than the baking temperature in the baking step. The baking temperature during the pre-baking step is, for example, in the range of 400° C. or higher and lower than 700° C. The pre-baking may be performed multiple times.
[0101] The firing apparatus used in the firing step and the pre-firing step is not particularly limited, and may be, for example, a continuous firing furnace or a fluidized firing furnace. The continuous firing furnace may be, for example, a tunnel furnace or a roller hearth kiln. The fluidized firing furnace may be, for example, a rotary kiln.
[0102] The fired product obtained in the firing step (ST20) may be crushed as appropriate, thereby producing a crushed fired product.
[0103] The fired product may be crushed multiple times. For example, when the firing step involves sequentially performing a first firing stage and a second firing stage, the fired product may be crushed after the first firing stage and then crushed again after the second firing stage.
[0104] [B-3] Post-processing process (ST40) In the post-treatment step (ST40), the fired product produced in the firing step (ST20) is subjected to post-treatment. Here, for example, a washing process is performed as the post-treatment. In the washing process, impurities are removed from the fired product using a washing liquid such as water, ion-exchanged water, an alkaline aqueous solution, or a sulfate aqueous solution. In the post-treatment, the slurry concentration is set to 40% or more, and the washing time is within a predetermined range. The washing time can be, for example, 5 minutes or more and less than 20 minutes. The slurry concentration means the ratio of the weight of the fired product (WS) to the total weight (WS+WL) of the fired product (WS) and the washing liquid (WL) (i.e., 100*WS / (WS+WL)(%)).
[0105] [B-4] Drying process (ST50) In the drying step (ST50), a drying process is carried out on the fired product that has been subjected to the post-treatment in the post-treatment step (ST40).
[0106] In the drying step (ST50), the fired product is dried in an atmosphere having a temperature of, for example, 100°C or higher and 400°C or lower. The drying temperature is preferably equal to or higher than the lower limit of the above range in order to prevent the charge capacity of the lithium secondary battery from decreasing due to moisture remaining in the CAM before drying. Therefore, the lower limit of the drying temperature is more preferably 110°C, and even more preferably 120°C or higher. Moreover, the drying temperature is preferably equal to or lower than the upper limit of the above range in order to prevent re-sintering of the grain boundaries of the CAM. Therefore, the upper limit of the drying temperature is more preferably 350°C, and particularly preferably 300°C.
[0107] The drying is performed, for example, by reduced pressure drying, vacuum drying, air blowing, heating, or a combination of these. Reduced pressure drying and vacuum drying are performed, for example, under conditions of 0.3 atm or less and at a temperature range of 100° C. to 200° C. Drying by air blowing is performed, for example, using a hot air dryer.
[0108] The dried powder may be mixed with a coating material raw material and then heat-treated. The coating material raw material may be, for example, an oxide, hydroxide, carbonate, sulfate, nitrate, halide, oxalate, or alkoxide of at least one element selected from the group consisting of Nb, Ge, Si, P, Al, W, Ta, Ti, S, Zr, Zn, V, and B, and is preferably an oxide.
[0109] The heat treatment conditions are adjusted according to the type of the coating material raw material. For example, the heat treatment temperature is 200°C or higher and 850°C or lower, and the heat treatment time is 3 hours or higher and 50 hours or lower. The atmosphere during the heat treatment can be air, oxygen, nitrogen, argon, or a mixed gas thereof.
[0110] Through the above steps, the CAM can be manufactured.
[0111] [C] Lithium secondary battery An example of a positive electrode for a lithium secondary battery having the CAM of this embodiment and a lithium secondary battery including the positive electrode for a lithium secondary battery will be described below. Hereinafter, the positive electrode for a lithium secondary battery may be referred to as a positive electrode.
[0112] An example of a suitable lithium secondary battery when using the CAM manufactured by the manufacturing method of this embodiment has a positive electrode and a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte solution disposed between the positive electrode and the negative electrode.
[0113] 3 is a schematic diagram showing an example of a lithium secondary battery. For example, a cylindrical lithium secondary battery 10 is manufactured as follows.
[0114] 3, a pair of belt-shaped separators 1, a belt-shaped positive electrode 2 having a positive electrode lead 21 attached to one end, and a belt-shaped negative electrode 3 having a negative electrode lead 31 attached to one end are prepared. Then, the separator 1, the positive electrode 2, the separator 1, and the negative electrode 3 are laminated in this order to form a laminate, which is then wound to produce an electrode group 4.
[0115] The positive electrode 2, for example, has a positive electrode active material layer 2a containing CAM, and a positive electrode current collector 2b on one surface of which the positive electrode active material layer 2a is formed. Such a positive electrode 2 can be manufactured by first preparing a positive electrode mixture containing CAM, a conductive material, and a binder, and supporting the positive electrode mixture on one surface of the positive electrode current collector 2b to form the positive electrode active material layer 2a.
[0116] Examples of the negative electrode 3 include an electrode in which a negative electrode mixture containing a negative electrode active material (not shown) is supported on a negative electrode current collector, and an electrode made of only the negative electrode active material. The negative electrode 3 can be manufactured in a manner similar to that for the positive electrode 2.
[0117] Next, the electrode group 4 and the insulator (not shown) are housed in a battery can 5, and the bottom of the battery can 5 is sealed. Then, the electrode group 4 is impregnated with an electrolyte solution 6 in the battery can 5, thereby interposing an electrolyte (not shown) between the positive electrode 2 and the negative electrode 3. Thereafter, the top of the battery can 5 is sealed with a top insulator 7 and a sealing body 8. In this way, a lithium secondary battery 10 is completed.
[0118] The shape of the electrode group 4 can be, for example, a columnar shape such that the cross-sectional shape when the electrode group 4 is cut perpendicular to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.
[0119] The shape of the lithium secondary battery having such an electrode group 4 may be any shape specified by IEC60086, a standard established by the International Electrotechnical Commission (IEC), or JIS C 8500. For example, cylindrical or rectangular shapes may be used.
[0120] Furthermore, the lithium secondary battery is not limited to the above-mentioned wound type configuration, and may be a laminated type configuration in which a laminated structure of a positive electrode, a separator, a negative electrode, and a separator is repeatedly stacked. Examples of the laminated type lithium secondary battery include a so-called coin type battery, a button type battery, and a paper type (or sheet type) battery.
[0121] For the positive electrode, separator, negative electrode, and electrolyte constituting the lithium secondary battery, for example, the configurations, materials, and manufacturing methods described in
[0113] to
[0140] of WO2022 / 113904A1 can be used.
[0122] [D] All-solid-state lithium secondary battery As an example of a lithium secondary battery including a positive electrode for a lithium secondary battery formed using the CAM of this embodiment, an all-solid-state lithium secondary battery will be described.
[0123] Fig. 4 is a schematic diagram showing an example of an all-solid-state lithium secondary battery. As shown in Fig. 4, the all-solid-state lithium secondary battery 1000 includes a laminate 100 having a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130, and an exterior body 200 that houses the laminate 100. The all-solid-state lithium secondary battery 1000 may have a bipolar structure in which a CAM and a negative electrode active material are disposed on both sides of a current collector. A specific example of the bipolar structure is the structure described in JP-A-2004-95400.
[0124] The positive electrode 110 has a positive electrode active material layer 111 and a positive electrode current collector 112. The positive electrode active material layer 111 contains the above-mentioned CAM and a solid electrolyte. The positive electrode active material layer 111 may also contain a conductive material and a binder.
[0125] The negative electrode 120 has a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains a negative electrode active material. The negative electrode active material layer 121 may also contain a solid electrolyte and a conductive material.
[0126] The laminate 100 may have an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122. In addition, the all-solid-state lithium secondary battery 1000 may have a separator between the positive electrode 110 and the negative electrode 120.
[0127] The all-solid-state lithium secondary battery 1000 further includes an insulator (not shown) that insulates the laminate 100 from the exterior body 200, and a sealing body (not shown) that seals the opening 200a of the exterior body 200.
[0128] Exterior body 200 is a container formed from a highly corrosion-resistant metal material such as aluminum, stainless steel, nickel-plated steel, etc. Exterior body 200 may also be a container formed into a bag shape from a laminate film having at least one surface treated to be corrosion-resistant.
[0129] The shape of the all-solid-state lithium secondary battery 1000 may be, for example, a coin type, a button type, a paper type (or a sheet type), a cylindrical type, a square type, or a laminate type (pouch type).
[0130] As an example, the all-solid-state lithium secondary battery 1000 has one laminate 100, but is not limited to this. The all-solid-state lithium secondary battery 1000 may have a configuration in which the laminate 100 is used as a unit cell, and a plurality of unit cells (laminates 100) are sealed inside the exterior body 200.
[0131] For the all-solid-state lithium secondary battery, for example, the configuration, materials, and manufacturing method described in
[0151] to
[0181] of WO2022 / 113904A1 can be used.
[0132] Another aspect of the present invention includes the following embodiments.
[11] A CAM containing Li, Ni, and the element X in its composition, the amount of substance of Li [Li], the amount of substance of Ni [Ni], and the amount of substance of the element X [X] satisfy the relationships shown in (Formula A1), (A2c), and (Formula A3), The CAM has, in the DTA curve, a first peak top located at a first temperature in a temperature range of 150°C or more and 300°C or less, and a second peak top located at a second temperature higher than the first temperature.
[12] The second temperature T2 satisfies the relationship shown in the above (Formula Ba).
[11] The CAM described in.
[13] The first temperature T1 and the second temperature T2 satisfy the relationship shown in the above (Formula Cb). The CAM according to
[11] or
[12] .
[14] A peak intensity P1 of the first peak top and a peak intensity P2 of the second peak top satisfy the relationship shown in the following (Formula Db). The CAM according to any one of
[11] to
[13] .
[15] The c-axis length L of the CAM satisfies the relationship shown in the above (Equation E). The CAM according to any one of
[11] to
[14] .
[16] D 50 satisfies the relationship shown in the following (Formula F), The CAM according to any one of
[11] to
[15] .
[17] The c-axis length L of the CAM satisfies the relationship shown in the above (Equation Ea). The CAM according to any one of
[11] to
[16] .
[18] D 80 satisfies the relationship shown in the following (Formula Fb), The CAM according to any one of
[11] to
[17] .
[19]
[11] to
[18] , Positive electrode for lithium secondary batteries.
[20]
[19] The positive electrode for a lithium secondary battery according to the present invention is provided. Lithium secondary battery. EXAMPLES
[0133] Examples and comparative examples will be described below with reference to Table 1. In Table 1, (Example 1) to (Example 4) correspond to examples, and (Example C1) and (Example C2) correspond to comparative examples.
[0134] [Table 1]
[0135] [1] Sample preparation The procedure for preparing the CAM samples for each example will be described in turn.
[0136] (Example 1) In Example 1, nickel-cobalt-manganese composite hydroxide (composition formula: Ni 0.83 Co 0.12 Mn 0.05 A powder of (OH)2) was prepared. The preparation of MCC was carried out by the continuous method described in JP 2002-201028 A.
[0137] Next, the lithium hydroxide monohydrate powder prepared as the lithium compound was mixed with the zirconium oxide powder and the MCC powder to obtain a mixture. Here, mixing was performed so that the value a0 obtained by dividing the amount of substance of Li [Li] by the sum of the amount of substance of Ni [Ni], the amount of substance of Co (= element X) [Co], the amount of substance of Mn (= element X) [Mn], and the amount of substance of Zr (= element X) [Zr] in the mixture would be the value shown in Table 1. (That is, a0 = [Li] / ([Ni] + [Co] + [Mn] + [Zr]) = 1.15)
[0138] Next, the powder mixture of MCC and the lithium compound was filled into a sagger, and then calcined in an oxygen atmosphere at a temperature of 650°C for 2 hours, and then the temperature was raised to 750°C and calcined for 5 hours.
[0139] Next, the obtained fired product was crushed.
[0140] Next, the crushed fired product was subjected to post-treatment. Here, the fired product was mixed with pure water in a weight ratio of 1:1 to prepare a slurry, which was then stirred for 20 minutes and dehydrated. The post-treatment was performed under the conditions of the slurry concentration and washing time shown in Table 1.
[0141] Next, the fired product that had been subjected to the post-treatment was dried at 190° C. to obtain Powder 1.
[0142] Then, powder 1 was mixed with boric acid powder. The mixing was carried out at a ratio of 1 mol% ([B] / ([Ni]+[Co]+[Mn]+[Zr]))*100=1 mol%) when the amount of substance of B element contained in boric acid [B] was divided by the sum of the amount of substance of Ni [Ni], the amount of substance of Co (=element X) [Co], the amount of substance of Mn (=element X) [Mn], and the amount of substance of Zr (=element X) [Zr] contained in powder 1.
[0143] The mixture of Powder 1 and boric acid powder was then filled into a sagger and heat-treated at 300° C. for 5 hours in an oxygen gas atmosphere to complete a CAM sample of this example.
[0144] (Example 2) In Example 2, nickel-cobalt-manganese composite hydroxide (composition formula: Ni 0.88 Co 0.09 Mn 0.03 A powder of (OH)2) was prepared. The preparation of MCC was carried out by the continuous method described in JP 2002-201028 A.
[0145] Next, the lithium hydroxide monohydrate powder prepared as the lithium compound was mixed with the MCC powder and the zirconium oxide powder to obtain a mixture. Here, mixing was performed so that the value a0 obtained by dividing the amount of substance of Li [Li] by the sum of the amount of substance of Ni [Ni], the amount of substance of Co (= element X) [Co], the amount of substance of Mn (= element X) [Mn], and the amount of substance of Zr (= element X) [Zr] in the mixture would be the value shown in Table 1.
[0146] Next, the powder mixture of MCC and the lithium compound was filled into a sagger, and then calcined for 2 hours at a temperature of 650°C in an oxygen atmosphere, and then calcined for 5 hours at a temperature of 720°C.
[0147] Next, in the same manner as in Example 1, the obtained fired product was crushed, post-treated, and dried to obtain Powder 2. The post-treatment was carried out under the conditions of the slurry concentration and washing time shown in Table 1.
[0148] Thereafter, in the same manner as in Example 1, Powder 2 and powder of boric acid were mixed, and the mixed powder was heat-treated to complete the CAM sample of this example.
[0149] (Example 3) In Example 3, nickel-cobalt-aluminum composite hydroxide (composition formula: Ni 0.88 Co 0.09 Al 0.03 A powder of (OH)2) was prepared. The preparation of MCC was carried out by the continuous method described in JP 2002-201028 A.
[0150] Next, the lithium hydroxide monohydrate powder prepared as a lithium compound was mixed with the MCC powder to obtain a mixture. Here, mixing was performed so that the value a0 obtained by dividing the amount of substance of Li [Li] by the sum of the amount of substance of Ni [Ni], the amount of substance of Co (=element X) [Co], and the amount of substance of Al (=element X) [Al] in the mixture would be the value shown in Table 1 (i.e., a0=[Li] / ([Ni]+[Co]+[Al])=1.11).
[0151] Next, the powder mixture of MCC and the lithium compound was filled into a sagger, and then calcined for 2 hours at a temperature of 650°C in an oxygen atmosphere, and then calcined for 5 hours at a temperature of 690°C.
[0152] Next, the obtained fired product was crushed.
[0153] Next, the crushed fired product was subjected to post-treatment. Here, the fired product was mixed with pure water in a weight ratio of 1:1 to prepare a slurry, which was then stirred for 20 minutes and dehydrated. The post-treatment was performed under the conditions of the slurry concentration and washing time shown in Table 1.
[0154] Next, the fired product that had been subjected to the post-treatment was dried at 190° C. to obtain powder 3.
[0155] Then, powder 3 was mixed with boric acid powder. The mixing was performed in such a ratio that the amount of substance [B] of element B contained in boric acid divided by the sum of the amount of substance [Ni] of Ni, the amount of substance [Co] of Co (=element X), and the amount of substance [Al] of Al (=element X) contained in powder 3 was 1 mol% ([B] / ([Ni]+[Co]+[Al])*100=1 mol%).
[0156] The mixture of Powder 1 and boric acid powder was then packed into a sagger and heat-treated at 300° C. for 5 hours in an oxygen gas atmosphere to complete a CAM sample of this example.
[0157] (Example 4) In Example 4, first, nickel-cobalt-manganese composite hydroxide (composition formula: Ni 0.85 Co 0.06 Mn 0.09 A powder of (OH)2) was prepared. The preparation of MCC was carried out by the continuous method described in JP 2002-201028 A.
[0158] Next, the lithium hydroxide monohydrate powder prepared as the lithium compound was mixed with the MCC powder and the zirconium oxide powder to obtain a mixture. Here, mixing was performed so that the value a0 obtained by dividing the amount of substance of Li [Li] by the sum of the amount of substance of Ni [Ni], the amount of substance of Co (= element X) [Co], the amount of substance of Mn (= element X) [Mn], and the amount of substance of Zr (= element X) [Zr] in the mixture would be the value shown in Table 1.
[0159] Next, the powder mixture of MCC and the lithium compound was filled into a sagger, and then calcined for 2 hours at a temperature of 650°C in an oxygen atmosphere, and then calcined for 5 hours at a temperature of 720°C.
[0160] Next, in the same manner as in Example 1, the obtained fired product was crushed, post-treated, and dried to obtain Powder 4. The post-treatment was carried out under the conditions of the slurry concentration and washing time shown in Table 1.
[0161] Thereafter, in the same manner as in Example 1, Powder 4 and powder of boric acid were mixed, and the mixed powder was heat-treated to complete the CAM sample of this example.
[0162] (Example C1) In (Example C1), the same nickel-cobalt-aluminum composite hydroxide (composition formula: Ni 0.83 Co 0.12 Al 0.05 (OH)2) powder was prepared as MCC.
[0163] Next, the lithium hydroxide monohydrate powder prepared as the lithium compound was mixed with the MCC powder to obtain a mixture. Here, mixing was performed so that the value a0 obtained by dividing the amount of substance of Li [Li] by the sum of the amount of substance of Ni [Ni], the amount of substance of Co (=element X) [Co], and the amount of substance of Al (=element X) [Al] in the mixture would be the value shown in Table 1. (That is, a0 = [Li] / ([Ni] + [Co] + [Al]) = 1.02)
[0164] Thereafter, similarly to the case of (Example 3), firing, crushing, post-treatment, drying, etc. were carried out in sequence to complete the CAM sample of this example. The post-treatment was carried out under the conditions of the slurry concentration and washing time shown in Table 1.
[0165] (Example C2) In (Example C2), nickel-cobalt-manganese composite hydroxide (composition formula: Ni 0.88 Co 0.8 Mn 0.4 A powder of (OH)2) was prepared. The preparation of MCC was carried out by the continuous method described in JP 2002-201028 A.
[0166] Next, the lithium hydroxide monohydrate powder prepared as the lithium compound was mixed with the MCC powder to obtain a mixture. Here, mixing was performed so that the value a0 obtained by dividing the amount of substance of Li [Li] by the sum of the amount of substance of Ni [Ni], the amount of substance of Co (= element X) [Co], and the amount of substance of Mn (= element X) [Mn] in the mixture would be the value shown in Table 1. (That is, a0 = [Li] / ([Ni] + [Co] + [Mn]) = 1.10)
[0167] Thereafter, similarly to the case of (Example 1), firing, crushing, post-treatment, drying, etc. were carried out in sequence to complete the CAM sample of this example. The post-treatment was carried out under the conditions of the slurry concentration and washing time shown in Table 1.
[0168] [2] Characteristics of the sample The composition and properties of the CAM samples prepared for each example were evaluated, and the results are shown in Table 1.
[0169] [2-1] Differential thermal analysis curve (DTA curve) Here, as shown in Table 1, a differential thermal analysis was carried out on the sample of each example, and a differential thermal analysis curve (DTA curve) was obtained.
[0170] When performing differential thermal analysis for each example, a positive electrode was prepared from the sample of each example, and then a coin-type half-cell lithium secondary battery was prepared using the prepared positive electrode. After that, the lithium secondary battery was charged, and the positive electrode was taken out by dismantling the lithium secondary battery. Then, a positive electrode mixture containing CAM was sampled from the positive electrode, and a differential thermal analysis curve was obtained by performing differential thermal analysis on the sampled positive electrode mixture.
[0171] The above items will be explained in detail below.
[0172] [2-1-1] Preparation of positive electrodes for lithium secondary batteries In the preparation of the positive electrode for lithium secondary batteries, a paste-like positive electrode mixture was first prepared. The positive electrode mixture was prepared by kneading a mixture of the CAM, conductive material, and binder prepared in each example. Here, acetylene black was used as the conductive material, and PVdF was used as the binder. Then, each material was mixed in the following ratio. When preparing the positive electrode mixture, N-methyl-2-pyrrolidone was used as the organic solvent.
[0173] ·CAM: 92 parts by mass ·Conductive material: 5 parts by mass Binder: 3 parts by weight
[0174] The paste-like positive electrode mixture prepared as above was applied to a current collector (aluminum foil with a thickness of 40 μm). After that, the current collector to which the positive electrode mixture was applied was vacuum-dried for 8 hours in an atmosphere at a temperature of 150° C., thereby completing a positive electrode for a lithium secondary battery. Here, the electrode area of the positive electrode for a lithium secondary battery was set to 1.65 cm2.
[0175] [2-1-2] Fabrication of lithium secondary battery (coin-type half cell) When preparing the lithium secondary battery, first, the lithium secondary battery positive electrode prepared as described above was placed on the upper surface of the lower cover of a coin battery R2032 part (manufactured by Hosen Co., Ltd.). When placing it on the lower cover, the aluminum foil surface of the lithium secondary battery positive electrode was facing downward. Then, a laminated film separator was placed on the upper surface of the lower cover on which the lithium secondary battery positive electrode was placed. Here, the laminated film separator used was one having a thickness of 16 μm and having a heat-resistant porous layer laminated on a polyethylene porous film.
[0176] Next, 300 μl of electrolyte was injected into the inside of the above parts. Here, the electrolyte used was a solution in which LiPF6 was dissolved in a mixture of the following substances in the following ratios. The electrolyte was prepared so that the concentration of LiPF6 was 1 mol / l.
[0177] Ethylene carbonate: 30 parts by volume Dimethyl carbonate: 35 parts by volume Ethyl methyl carbonate: 35 parts by volume
[0178] Next, the negative electrode was placed on the top of the separator. Metallic lithium was used as the negative electrode. Then, a top cover was placed via a gasket and the top cover was crimped using a crimping machine. This produced a coin-type half cell R2032 as a lithium secondary battery.
[0179] [2-1-3] Charging secondary lithium batteries The lithium secondary battery was charged and discharged for the first time under the following conditions. After the first charge and discharge, the lithium secondary battery was charged and discharged for the second time under the following conditions.
[0180] (Initial charge / discharge conditions) Processing temperature: 25℃ Maximum charging voltage: 4.3V, charging current: 0.1C, constant current / constant voltage charging, end current: 0.025C Minimum discharge voltage: 2.5V, discharge current: 0.1C, constant current discharge
[0181] (Second charge) Maximum charging voltage 4.3V, charging current 0.1C, constant current constant voltage charging, end current 0.025C
[0182] [2-1-4] Dismantling of lithium secondary batteries The lithium secondary battery was disassembled in a glove box with an argon gas atmosphere. Here, the lithium secondary battery was disassembled using a dismantling machine so as not to short-circuit the positive electrode and the negative electrode in the charged lithium secondary battery, and the positive electrode was removed from the lithium secondary battery.
[0183] [2-1-5] Extraction of positive electrode mixture When extracting the positive electrode mixture, first, the positive electrode removed from the lithium secondary battery was washed to remove the electrolyte adhering to the positive electrode. Dimethyl carbonate (DMC) was used as the washing solution. The washed positive electrode was then dried to remove the purified electrolyte adhering to the positive electrode. After that, in a glove box with an argon gas atmosphere, the positive electrode mixture containing CAM was extracted from the positive electrode. To extract the positive electrode mixture, the positive electrode mixture applied to the Al foil in the positive electrode was scraped off using ceramic tweezers.
[0184] [2-1-6] Performing differential thermal analysis Differential thermal analysis was performed on each positive electrode mixture using a simultaneous differential thermal and thermogravimetric analyzer (STA7300; Hitachi High-Tech Corporation) under the following conditions: The differential thermal analysis was performed under conditions that allowed evaluation of the thermal decomposition of CAM.
[0185] · Upper limit of measurement temperature: 400℃ Heating rate: 5℃ / min Measurement atmosphere: Nitrogen gas flow Positive electrode mixture weight: 10mg Measuring container: Metal aluminum pan
[0186] As a result, a differential thermal analysis curve (DTA curve) was obtained for each sample.
[0187] Then, as shown in Table 1, the "number of peak tops" present in the temperature range of 150° C. or more and 300° C. or less in the DTA curve was determined.
[0188] FIG. 5 is a diagram showing DTA curves obtained for (Example 1) and (Example C1).
[0189] As shown in FIG. 5, Example 1 had two "peak tops." In contrast, Example C1 had one "peak top." Although differential thermal analysis curves (DTA curves) are not shown for the other examples, as shown in Table 1, Example 2 and Example 3 had two "peak tops," just like Example 1, and Example C2 had one "peak top," just like Example C1.
[0190] Then, when the "number of peak tops" is two, the first temperature T1 at which the first peak top PT1 on the low temperature side is located and the second temperature T2 at which the second peak top PT2 on the high temperature side is located were determined, as shown in Table 1. At the same time, the peak intensity P1 of the first peak top PT1 and the peak intensity P2 of the second peak top PT2 were determined.
[0191] [2-2]c-axis length L As shown in Table 1, the c-axis length L of the CAM samples prepared for each example was calculated from the lattice constant of the CAM.
[0192] The lattice constant was obtained by performing powder X-ray diffraction measurement on the sample using an X-ray diffractometer (eg, D8ADVANCE manufactured by Bruker).
[0193] Specifically, the powder of the sample was filled into a dedicated substrate, and then a powder X-ray diffraction pattern was obtained by measuring under the following conditions using a Cu-Kα radiation source.
[0194] Diffraction angle 2θ: 10°~90° Sampling width: 0.02°
[0195] The powder X-ray diffraction pattern was then analyzed using integrated powder X-ray analysis software (e.g., TOPAS), and the crystal structure was refined to a layered rock salt structure belonging to the space group R-3m to determine the c-axis length L.
[0196] [2-3] 50% cumulative volumetric grain size D 50 As shown in Table 1, for the CAM samples prepared for each example, D 50 asked for.
[0197] D 50 The measurement of was carried out by the laser diffraction scattering method. Specifically, first, a dispersion liquid was obtained by dispersing the sample powder. The dispersion liquid was prepared by putting 0.1 g of CAM powder into 50 ml of sodium hexametaphosphate aqueous solution (concentration: 0.2 mass%). Next, a laser diffraction scattering particle size distribution measuring device (Microtrack MT3300EXII, manufactured by Microtrack Bell Co., Ltd.) was used to measure the particle size distribution of the powder in the dispersion liquid, thereby obtaining a cumulative particle size distribution curve based on volume. Then, D was calculated from the cumulative particle size distribution curve. 50 The values of (μm) were obtained.
[0198] The composition of the CAM was measured by dissolving the CAM in an acid or alkali and using an ICP emission spectrometer (Optima 7300, manufactured by PerkinElmer Co., Ltd.).
[0199] [3] Battery evaluation As described above, the CAM samples prepared in each example were subjected to battery evaluation as shown in Table 1. Here, the "60°C cycle retention rate" was measured as the battery evaluation.
[0200] When conducting the battery evaluation, a coin-type full-cell lithium secondary battery was fabricated using the positive electrode fabricated from each CAM sample as described above. Then, for the fabricated lithium secondary battery, the "60°C cycle retention rate" was measured as a battery evaluation, as shown in Table 1, in order to evaluate the cycle characteristics at high temperatures.
[0201] The above will be described in detail below.
[0202] [3-1] Fabrication of lithium secondary battery (coin type full cell) When preparing the lithium secondary battery, first, the positive electrode prepared using the sample of each example was placed on the upper surface of the bottom cover of a part for a coin-type battery CR2032 (manufactured by Hosen Co., Ltd.). When placing it on the bottom cover, the aluminum foil surface of the positive electrode for the lithium secondary battery was facing downward. Then, a laminated film separator was placed on the upper surface of the bottom cover on which the positive electrode was placed. Here, the laminated film separator used was one having a thickness of 16 μm and having a heat-resistant porous layer laminated on a polyethylene porous film.
[0203] Next, 300 μl of electrolyte was injected into the inside of the above parts. Here, the electrolyte was a solution in which the following materials were mixed in the following ratio, to which 1% by volume of vinylene carbonate was added, and further LiPF6 was dissolved. The electrolyte was prepared so that the concentration of LiPF6 was 1.3 mol / l.
[0204] Ethylene carbonate: 16 parts by volume Dimethyl carbonate: 10 parts by volume Ethyl methyl carbonate: 74 parts by volume
[0205] Next, the negative electrode was placed on the top of the separator. Here, a graphite particle coated electrode foil (graphite particle weight 98% of the total weight of the coated electrode foil) was used as the negative electrode. Then, a top cover was placed via a gasket, and the top cover was crimped using a crimping machine. In this way, a coin-type full cell CR2032 was produced as a lithium secondary battery.
[0206] [3-2] Measurement of "60℃ cycle maintenance rate" In measuring the "60°C cycle retention rate (%)," a cycle test was performed in which a "charge and discharge test" was repeated 50 times on a coin-type full-cell lithium secondary battery at a test temperature of 60°C. The "60°C cycle retention rate (%)" was calculated by dividing the discharge capacity measured in the 50th cycle of the "charge and discharge test" by the discharge capacity measured in the 1st cycle of the "charge and discharge test."
[0207] Specifically, a charge / discharge test was repeatedly carried out under the following conditions. Test temperature: 60℃ Maximum charging voltage 4.2V, charging current 1CA, constant current constant voltage charging, end current 0.05C Minimum discharge voltage 2.5V, discharge current 2CA, constant current discharge
[0208] [4] Summary The results of each example are explained.
[0209] [4-1] Results of (Example 1) to (Example 4) As shown in Table 1, in (Example 1) to (Example 4), the composition of the CAM satisfies the relationships shown in the above (Formula A1) to (Formula A3).
[0210] The DTA curves of the CAM in (Example 1) to (Example 4) have two peak tops. The two peak tops are a first peak top PT1 located at a first temperature T1 and a second peak top PT2 located at a second temperature T2 higher than the first temperature T1.
[0211] As a result, it was found that the lithium secondary batteries of (Example 1) to (Example 4), as shown in the "Evaluation" column of Table 1, had a high 60°C cycle retention rate (%) and excellent cycle characteristics at high temperatures.
[0212] [4-2] Regarding the results of (Example C1) and (Example C2) In (Example C1) and (Example C2), the DTA curve of CAM has one peak top, as shown in Table 1. Therefore, unlike (Example 1) to (Example 4), (Example C1) and (Example C2) do not have Li introduced into two different sites, and the CAM structure is not stable during lithium ion insertion and removal. Therefore, it was found that the cycle characteristics at high temperatures are inferior to those of (Example 1) to (Example 4). [Industrial Applicability]
[0213] According to the present invention, it is possible to provide a positive electrode active material for a lithium secondary battery, a positive electrode for a lithium secondary battery, a lithium secondary battery, and a method for producing a positive electrode active material for a lithium secondary battery, which can easily realize a lithium secondary battery having excellent cycle characteristics at high temperatures. [Explanation of symbols]
[0214] Reference Signs List 1...separator, 2...positive electrode, 2a...positive electrode active material layer, 2b...positive electrode current collector, 3...negative electrode, 4...electrode group, 5...battery can, 6...electrolyte, 7...top insulator, 8...sealing body, 10...lithium secondary battery, 21...positive electrode lead, 31...negative electrode lead, 100...laminated body, 110...positive electrode, 111...positive electrode active material layer, 112...positive electrode current collector, 113...external terminal, 120...negative electrode, 121...negative electrode active material layer, 122...negative electrode current collector, 123...external terminal, 130...solid electrolyte layer, 200...exterior body, 200a...opening, 1000...all-solid-state lithium secondary battery
Claims
1. The composition contains Li, Ni, and an element X, The element X is at least one element selected from the group consisting of Co, Al, Mg, Ca, Si, Fe, Cr, V, Mo, W, Nb, Ti, Zr, Ta, Mn, and B; A positive electrode active material for a lithium secondary battery, comprising: The amount of substance of Li [Li], the amount of substance of Ni [Ni], and the amount of substance of the element X [X] satisfy the relationships shown in the following (Formula A1) to (Formula A3), A lithium secondary battery prepared using the positive electrode active material for lithium secondary batteries was charged at 4.3 V (vs. Li + / Li), and then a differential thermal analysis curve obtained by performing a differential thermal analysis on the positive electrode mixture contained in the charged lithium secondary battery under an inert gas atmosphere has a first peak top located at a first temperature in a temperature range of 150° C. or more and 300° C. or less, and a second peak top located at a second temperature higher than the first temperature, Positive electrode active material for lithium secondary batteries. [Li]:[Ni]:[X]=a:(1-b):b...(Formula A1) 0.95≦a≦1.2…(Formula A2) 0<b≦0.3...(Formula A3)
2. The second temperature T2 satisfies the relationship shown in the following (Formula B): The positive electrode active material for a lithium secondary battery according to claim 1 . 235℃≦T2≦285℃…(Formula B)
3. The first temperature T1 and the second temperature T2 satisfy the relationship shown in the following (Formula C). The positive electrode active material for a lithium secondary battery according to claim 1 or 2. 1.06≦T2 / T1≦1.40...(Formula C)
4. The peak intensity P1 of the first peak top and the peak intensity P2 of the second peak top satisfy the relationship shown in the following (Formula D). The positive electrode active material for a lithium secondary battery according to claim 1 or 2. 0<P2 / P1≦1.0…(Formula D)
5. The c-axis length L of the positive electrode active material for a lithium secondary battery satisfies the relationship shown in the following (Formula E), The positive electrode active material for a lithium secondary battery according to claim 1 or 2. 14.160Å≦L≦14.210Å…(Formula E)
6. 50% cumulative volumetric particle size D 50 satisfies the relationship shown in the following (Formula F), The positive electrode active material for a lithium secondary battery according to claim 1 or 2. 5μm≦D 50 ≦25μm …(Formula F)
7. The positive electrode active material for a lithium secondary battery according to claim 1 or 2, Positive electrode for lithium secondary batteries.
8. The positive electrode for a lithium secondary battery according to claim 7, Lithium secondary battery.
Citation Information
Patent Citations
Positive electrode active material for nonaqueous electrolyte secondary battery, method for manufacturing the same, and nonaqueous electrolyte secondary battery
JP2018049685A
Positive electrode active material for lithium ion secondary battery, method for manufacturing positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery
WO2020175552A1